In vitro Anti-oxidative Activity and Tyrosinase Inhibition of Inca Peanut (Plukenetia volubilis L.) Shell Extracts from Different Preparation Methods - Sainakham, Mathukorn; Mungmai, Lapatrada (Thai Journal of Science and Technology, 2020)
In the present investigation, the bioactivities of the inca peanut (Plukenetia volubilis L.) shell extracts prepared by various methods were determined for food and cosmetic applications. The inca peanut shells were extracted and determined total phenolic content, anti-oxidation by DPPH assay, tyrosinase inhibition and phytochemical analysis. The results showed that the extract from non-cooked shell before extracting by the hot mixture of water and ethanol (NM2) gave the highest total phenolic content at 129.95±7.58 mg GAE/g and the highest free radical scavenging activity at SC50 of 0.12±0.03 mg/mL. The highest inhibition of tyrosinase activity was presented by the extract from roasted shell before extracting by cold ethanol (RE1) at IC50 of 6.90±1.40 mg/mL. In addition, the selected extracts contained the phytochemical contents of flavonoids and triterpenoids. This study has demonstrated the anti-oxidation and tyrosinase inhibition potential of the inca peanut shell extracts.